EXPERIMENTAL STUDY HEAT EXCHANGER NEW DESIGN - Gorobets, V.; Trokhanyak, V.; Bogdan, Y. (Energy and Automation, 2016)
Designed and built an experimental setup based on heat exchangers of a new design with a compact placement of tube bundles in which the coolant is used as cooling water from underground wells. A comparison of the results of a numerical calculation of mathematical modeling and experimental data on heat transfer tube bundle by statistical analysis.